Temperature effect corrections for URAGAN based on CAO, GDAS, NOAA data. (July 2015) - Dmitrieva, A; Ampilogov, N; Astapov, I; Barbashina, N; Borog, V; Chernov, D; Kovylyaeva, A; Kokoulin, R; Kompaniets, K; Mannocchi, G; Mishutina, Yu; Petrukhin, A; et al.
Abstract: For the analysis of muon flux variations caused by extra-atmospheric processes it is necessary to introduce corrections for meteorological effects. For temperature effect (TE) correction it is necessary to know the temperature profile of the atmosphere. As a rule, this profile is measured by meteorological balloons two or four times a day. Alternative sources are satellite observations and data obtained from models of atmosphere used for weather forecasting. Vertical temperature profiles obtained from NOAA satellites, GDAS (Global Data Assimilation System) and CAO data (Central Aerological Observatory, Russia) for standard isobaric levels were compared. Mean value of temperature difference for most levels does not exceed 1 K. Comparison of URAGAN data corrected for TE with CAO information, satellites and GDAS shows a good agreement. Counting rate and anisotropy of the muon flux corrected for meteorological effects for 2007-2014 are presented.